2007
DOI: 10.1253/circj.71.1328
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Target Lesion Revascularization and Documented Stent Thrombosis Beyond 30 Days After Sirolimus-Eluting Stent Implantation Retrospective Analysis in Consecutive 1,070 Angiographic Follow-up Lesions

Abstract: Background Outcomes after sirolimus-eluting stent (SES: Cypher ® ) implantation remained to be elucidated in Japan. Methods and Results Among 1,070 consecutive angiographic follow-up lesions, 99 lesions underwent target lesion revascularization (TLR) with in-stent restenosis (ISR). Retrospective estimation by multivariate analysis including 50 variables showed that the ostiums of right coronary and left circumflex arteries, hemodialysis, calcification, non-direct stenting, ISR of SES, and non-eccentric lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…18,19) These would be attributable to the present better angiographic outcomes of EES by attenuating the impact of those factors on the present angiographic endpoints. Thus, the present multicenter-study, which recruited more than 3000 lesions followed-up angiographically that included high propensity and complex lesions for ISR treated in a daily practice environment, could first show overall better midterm angiographic outcomes for EES over SES.…”
Section: Discussionmentioning
confidence: 97%
“…18,19) These would be attributable to the present better angiographic outcomes of EES by attenuating the impact of those factors on the present angiographic endpoints. Thus, the present multicenter-study, which recruited more than 3000 lesions followed-up angiographically that included high propensity and complex lesions for ISR treated in a daily practice environment, could first show overall better midterm angiographic outcomes for EES over SES.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of reports showing long-term clinical outcomes of late reperfusion in STEMI patients using both DES and BMS, including invasive therapy, plays a role in these guidelines. The present paper sought to evaluate the safety and efficacy of widelyspread late reperfusion in STEMI patients using emergent procedures based on recent advances in operator skill and PCI modalities in Japan, where the incidence of severe cardiac events, such as stent thrombosis, is less frequent than that observed in Western countries (2,3,7,8). The present study reflects the clinical setting and included high-risk patients with complex lesions consistently related to cardiac events and binary restenosis, such as those with cardiac dysfunction, Killip 3-4 classifications, severe calcification, LAD ostium and thrombus-containing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Japanese Circulation Society (JCS) guidelines for the management of STEMI patients state that there is little evidence for the long-term safety of drug-eluting stent (DES) use for primary stenting in STEMI patients (6). Therefore, it is necessary to examine the long-term safety of SES for the treatment of STEMI patients in Japan, where the incidence of severe cardiac events, such as stent thrombosis, is less frequent than that observed in Western countries (2,3,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…10,[22][23][24][25][26] The target lesion and stent delivery route CAC scores were also included. As shown in Table 3 summarizing multivariate analysis, the CAC score of the stent delivery route was independently associated with restenosis (odds ratio of 6.804, P<0.05), although CAC score of the target lesion was not.…”
Section: Comparisons Of Calcification Score Analysismentioning
confidence: 99%
“…However, the restenosis rate following SES implantation was still low, 7.3% in this study, which was comparable to that observed in many other studies. [8][9][10]22,23 Recently, SES application has been spreading widely, for example, for the left main lesion; 11 thus, it has become more important to clarify the factors associated with restenosis of SES, even though the prevalence is low.…”
Section: Restenosis Following Sesmentioning
confidence: 99%